When f(x) = x³ + 3x² – kx + 4 is divided by (x – 2), the remainder is k.i) Find the value of k.ii) Check (x – 1) is a factor of f(x).
Answers
Answered by
1
➡️Answer:
k= 12
(x-1) is not a factor of f(x)
➡️Solution:
i) Find the value of k:
![(x - 2) \: is \: a \: factor \: of \: {x}^{3} + 3 {x}^{2} - kx + 4 \\ (x - 2) \: is \: a \: factor \: of \: {x}^{3} + 3 {x}^{2} - kx + 4 \\](https://tex.z-dn.net/?f=%28x+-+2%29+%5C%3A+is+%5C%3A+a+%5C%3A+factor+%5C%3A+of+%5C%3A+%7Bx%7D%5E%7B3%7D+%2B+3+%7Bx%7D%5E%7B2%7D+-+kx+%2B+4+%5C%5C+)
than it divides completely,i. e. Remainder will be zero
![x - 2) {x}^{3} + 3 {x}^{2} - kx + 4( {x}^{2} + 5x + 10 - k \\ \: \: \: \: \: \: \: \: \: \: \: \: {x}^{3} - 2 {x}^{2} \\ - - - - - - - - change \: sign\\ \: \: \: \: \: \: \: \: \: 5 {x}^{2} - kx \\ \: \: \: \: \: \: \: \: \: \: \: 5 {x}^{2} - 10x \\ - - - - - - - - - - \\ \: \: \: \: \: \: \: \: (10 - k)x + 4 \\ \: \: \: \: \: \: \: \: \: (10 - k)x - 20 + 2k \\ \: \: \: \: \: \: \: \: - - - - - - - - \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 24 - 2k \\ x - 2) {x}^{3} + 3 {x}^{2} - kx + 4( {x}^{2} + 5x + 10 - k \\ \: \: \: \: \: \: \: \: \: \: \: \: {x}^{3} - 2 {x}^{2} \\ - - - - - - - - change \: sign\\ \: \: \: \: \: \: \: \: \: 5 {x}^{2} - kx \\ \: \: \: \: \: \: \: \: \: \: \: 5 {x}^{2} - 10x \\ - - - - - - - - - - \\ \: \: \: \: \: \: \: \: (10 - k)x + 4 \\ \: \: \: \: \: \: \: \: \: (10 - k)x - 20 + 2k \\ \: \: \: \: \: \: \: \: - - - - - - - - \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 24 - 2k \\](https://tex.z-dn.net/?f=x+-+2%29+%7Bx%7D%5E%7B3%7D+%2B+3+%7Bx%7D%5E%7B2%7D+-+kx+%2B+4%28+%7Bx%7D%5E%7B2%7D+%2B+5x+%2B+10+-+k+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%7Bx%7D%5E%7B3%7D+-+2+%7Bx%7D%5E%7B2%7D+%5C%5C+-+-+-+-+-+-+-+-+change+%5C%3A+sign%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+5+%7Bx%7D%5E%7B2%7D+-+kx+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+5+%7Bx%7D%5E%7B2%7D+-+10x+%5C%5C+-+-+-+-+-+-+-+-+-+-+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%2810+-+k%29x+%2B+4+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%2810+-+k%29x+-+20+%2B+2k+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+-+-+-+-+-+-+-+-+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+24+-+2k+%5C%5C+)
So
![24 - 2k = 0 \\ \\ 2k = 24 \\ \\ k = 12 \\ 24 - 2k = 0 \\ \\ 2k = 24 \\ \\ k = 12 \\](https://tex.z-dn.net/?f=24+-+2k+%3D+0+%5C%5C+%5C%5C+2k+%3D+24+%5C%5C+%5C%5C+k+%3D+12+%5C%5C+)
Now the polynomial is
![f(x) = {x}^{3} + 3 {x}^{2} - 12x + 4 \\ f(x) = {x}^{3} + 3 {x}^{2} - 12x + 4 \\](https://tex.z-dn.net/?f=+f%28x%29+%3D+%7Bx%7D%5E%7B3%7D+%2B+3+%7Bx%7D%5E%7B2%7D+-+12x+%2B+4+%5C%5C+)
2) If (x-1) is a factor of f(x) ,so on putting x=1, it becomes zero
![f(1) = {(1)}^{3} + 3( {1)}^{2} - 12(1) + 4 \\ \\ = 1 + 3 - 12 + 4 \\ \\ f(1)= - 4 \\ \\ f(1) = {(1)}^{3} + 3( {1)}^{2} - 12(1) + 4 \\ \\ = 1 + 3 - 12 + 4 \\ \\ f(1)= - 4 \\ \\](https://tex.z-dn.net/?f=f%281%29+%3D+%7B%281%29%7D%5E%7B3%7D+%2B+3%28+%7B1%29%7D%5E%7B2%7D+-+12%281%29+%2B+4+%5C%5C+%5C%5C+%3D+1+%2B+3+-+12+%2B+4+%5C%5C+%5C%5C+f%281%29%3D+-+4+%5C%5C+%5C%5C+)
No, (x-1) is not a factor of f(x)
Hope it helps you.
k= 12
(x-1) is not a factor of f(x)
➡️Solution:
i) Find the value of k:
than it divides completely,i. e. Remainder will be zero
So
Now the polynomial is
2) If (x-1) is a factor of f(x) ,so on putting x=1, it becomes zero
No, (x-1) is not a factor of f(x)
Hope it helps you.
Answered by
0
Answer:
Step-by-step explanation:
Concept:
Factor theorem:
(x-a) is a factor of f(x) if and only if f(a)=0
Remainder theorem;
when f(x) is divided by (x-a), the remainder is f(a)
1. f(x) = x³ + 3x² – kx + 4
The remainder when f(x) is divided by (x-2) is k
By remainder theorem,
f(2)=k
(2)³ + 3(2)² – k(2) + 4 = k
8+12-2k +4 = k
24 - 2k= k
24 = 3k
k=8
2.. f(x) = x³ + 3x² – kx + 4
put x=1,
f(1) = (1)³ + 3(1)² – 8(1) + 4
f(1) = 1+3-8+4 =0
since f(1)=0, by factor theorem
(x-1) is a factor of f(x)
Similar questions